A preliminary study of survival rates in civil aircraft accidents, 1966 - 1973, with particular reference to fire risk and fuel type - Taylor, A. F. (Cranfield Institute of Technology, 1974)
To establish whether theoretical and laboratory safety advantages of low volatily fuel, such as that of low rate of flame spread, are reflected in aircraft accident 'statistics' a preliminary study has been made of the ARB's world airline accident summary. An advantage has been found in that the change to kerosine has apparently halved the death rate in survivable accidents. In all gas turbine accidents, including those where death was probably due to impact not fire, the death rate seems to be 50% higher with wide cut gasoline than with kerosine. It has also been found that a higher proportion of gasoline powered aircraft accidents involved impact death 1.1-1d that overall the survival rate has remained virtually unchanged. A critical examination of these preliminary findings, in the light of the relevant accident reports, is planned.